LAITY IN THE LEGISLATION OF THE ROMANIAN ORTHODOX CHURCH - BARBU, Ștefan (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2016)
The present study analyzes the role and the rights of the laity, in various Statutes of the Romanian Orthodox Church. The present study shows that within the Romanian Patriarchate there are two different approaches concerning the extent of the involvement of the laity in the three-fold ministry of the Church, in particular as to its role in the field of Church governance. Thus, on the one hand one sees a strong tendency to limit the laity’s role and rights in the governing of the local Church (the diocese) or at the supra-local level (the Metropolis or the Patriarchate). On the other hand, there is another position that allows a greater involvement of the laity in the governing of the Church. The lack of laity’s involvement in the recently held Pan-Orthodox Council determines us to look again and critical to the situation within the ROC and argue for a return to an old and ecclesiologically sound canonical practice of total integration and active participation of the laity in the Church.